The role of pKa, log P of analytes, and protein matrix in solid-phase extraction using native and coated nanofibrous and microfibrous polymers prepared via meltblowing and combined meltblowing/electrospinning technologies - Raabová, Hedvika; Erben, Jakub; Chvojka, Jiří; Solich, Petr; Švec, František; Šatínský, Dalibor (Talanta, 2021)
Effect of physicochemical properties including dissociation constant (pKa) and partition coefficient (log P) of the compounds on their extraction efficiency in sample preparation using fibrous polymer sorbents has been demonstrated. Poly-ε-caprolactone as meltblown/electrospun composite fibers, and polypropylene, polyethylene, poly(3-hydroxybutyrate), poly(lactic acid), and polyamide 6 in the meltblown fiber format were used as sorbents in solid-phase extraction. In addition, the polycaprolactone fibers were coated with dopamine, dopamine combined with heparin, and tannin, respectively, to modify their extraction properties. These fibers that were not yet used for extractions and the unique combination of sorbents and analytes significantly extends the scope of nanofibrous extraction. The extraction efficiency was determined using model pharmaceuticals including acetylsalicylic acid, moxonidine, metoprolol, propranolol, propafenone, diltiazem, atorvastatin, and amiodarone. These model compounds displayed the widest differences in both pKa and log P values. The extraction efficiency of some of the fibers reached 96.64%. Coating of polycaprolactone fibers with dopamine significantly improved extraction efficiency of slightly retained metoprolol while moxonidine was not retained on any sorbent. The fibrous sorbents were also tested for extraction of pharmaceuticals in bovine serum albumin and human serum, respectively, to demonstrate their capability to extract them from a complex protein-containing matrix. The clean-up efficiency of our fibers was compared with that of a commercial restricted access media (RAM) C-18 alkyl-diol silica column. Our technique is in accordance with the requirements of modern sample preparation techniques.
Keywords: Proteins; Solid Phase Extraction; extrakce na pevné fázi; polymery; Electrospinning; Solid-phase extraction; Polymers; Column-switching; Fibers; Humans; nanovlákna; On-line sample preparation; lidé; proteiny; Nanofibers; Meltblown; Coating